2018
DOI: 10.4028/www.scientific.net/ssp.271.98
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Order and Static Displacements in Polycrystalline Ni-13.1at. %W Alloy

Abstract: A methodology accounting for the contributions of static displacements of atoms to X-ray diffuse scattering by binary solid solutions with a face-centered cubic lattice was proposed. By microscopic accounting of static displacements of the atoms on the particular shell, we identified short- range order parameters on the first eight shells of Ni-13.1at. %W alloy from the intensity of X-ray diffuse scattering. The Fourier transform of static displacement of the atoms on every considered shell was calculated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In general, good agreement was obtained between our phonon spectrum for nickel with the experimental measurements in [2]. Taking the larger number of spheres than the first four spheres in the equations of the dynamic matrix elements into account, it is impossible to improve the description of the experimental spectrum; the elastic constants that were calculated by equations from [9] vary noticeably from the experi- Table 1. The radial and tangential force constants for nickel (10 -3 The phonon spectrum for nickel at 296 K. The experimental data from [2] are highlighted with squares; the solid lines correspond to the calculated phonon branches with account for radial and tangential force constants in the first four coordination spheres.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…In general, good agreement was obtained between our phonon spectrum for nickel with the experimental measurements in [2]. Taking the larger number of spheres than the first four spheres in the equations of the dynamic matrix elements into account, it is impossible to improve the description of the experimental spectrum; the elastic constants that were calculated by equations from [9] vary noticeably from the experi- Table 1. The radial and tangential force constants for nickel (10 -3 The phonon spectrum for nickel at 296 K. The experimental data from [2] are highlighted with squares; the solid lines correspond to the calculated phonon branches with account for radial and tangential force constants in the first four coordination spheres.…”
Section: Resultssupporting
confidence: 63%
“…This agrees with the results in [2], where it was possible to estimate the Born-von Karman force constants on the first four coordination spheres using the phonon spectrum for nickel, and it was concluded that the smooth branches of the experimental phonon spectrum indicate the short-term actions of interatomic forces in nickel. Meanwhile, the theoretical calculations of the phonon spectrum and elastic constants for nickel using the pseudopotential method take the force constants on the first ten spheres into account [6,9]. According to the procedure that was described in [9], using the Animalu model potential of transition metals [9] we calculated the radial α i and tangential β i force constants for nickel on the first ten coordination spheres at the lattice constant a = 3.5239 Å, whose values are summarized in Table 1 in comparison with the calculations in [6] and with the values that were obtained using the phonon spectrum in this work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations